2016
DOI: 10.4070/kcj.2016.46.6.851
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transcatheter Atrial Septal Defect Closure in Children, Adolescents and adults: Differences, Challenges and Short-, Mid- and Long-Term Results

Abstract: Background and ObjectivesThis study aims to compare the characteristics, effectiveness and results of transcatheter closure of atrial septal defect between children, adolescents, and adults.Subjects and MethodsIn this study, 683 patients who underwent atrial septal defect closure in the last 10 years were divided into three groups: children (age <12), adolescents (age 12 to 16), and adults (age >16) as group 1, group 2 and group 3, respectively.ResultsThe average defect size and incidence of complex atrial sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 9) 10) The prevalence rate of complications is favorable, as it is 1% in the case of transcatheter ASD closure. 11) 12) 13) Accordingly, transcatheter secundum ASD closure is preferred over surgery and is being attempted at a younger age; 2) 14) 15) 16) however, recent studies reported both lower periprocedural success rates and an increased risk of periprocedural and long-term complications with the use of transcatheter closure either when body weight is ≤15 kg or in the presence of a large secundum ASD (≥20 mm/m 2 ). 11) 17) 18) Therefore, for improved procedural success rates and reduced complication rates, it is reasonable to delay the procedure until the weight is approximately 15 kg.…”
Section: Discussionmentioning
confidence: 99%
“… 9) 10) The prevalence rate of complications is favorable, as it is 1% in the case of transcatheter ASD closure. 11) 12) 13) Accordingly, transcatheter secundum ASD closure is preferred over surgery and is being attempted at a younger age; 2) 14) 15) 16) however, recent studies reported both lower periprocedural success rates and an increased risk of periprocedural and long-term complications with the use of transcatheter closure either when body weight is ≤15 kg or in the presence of a large secundum ASD (≥20 mm/m 2 ). 11) 17) 18) Therefore, for improved procedural success rates and reduced complication rates, it is reasonable to delay the procedure until the weight is approximately 15 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter closure of the intra cardiac shunt and defects is a safe and effective therapy [6]; however, hemolysis might occur after device implantation, which is mostly due to incomplete closure and residual flow [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported early after device closure of VSD and ASD, which emphasize the exact selection of the device size and type. If hemolysis and hemoglobin drop is persistent and does not resolve spontaneously, the device must be removed via intervention or operation [6, 7]. Here, we described incidence and outcome of hemolysis after transcatheter closure of these defects in our center.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous retrieval is successful in 50-75% cases, pulmonary artery and aorta being the easiest sites from which to retrieve. Another database reported 77.2% cases of surgical retrieval and 16.7% by percutaneous technique [9,10].…”
Section: Discussionmentioning
confidence: 99%